2023
DOI: 10.3389/fpls.2023.1083177
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the genetic potential of native rice (Oryza sativa L.) landraces for tolerance to early-stage submergence

Aravindan Shanmugam,
Kalaiarasan Manivelan,
Konne Deepika
et al.

Abstract: Direct-seeded rice (DSR) is a promising alternative to the traditional puddled rice system. It has become more popular among rice growers as a result of socioeconomic shifts and global climate change. Although DSR offers advantages, rice plants experience greater anaerobic stress at sowing from unpredicted rainfall. Rice is unique among cereals in its ability to germinate under anaerobiosis. The coleoptile of rice rapidly elongates above the water surface to obtain more oxygen and enhance vigorous seedling gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Twenty-one days is a commonly used duration for AG evaluation under flooded soil conditions ( Ismail et al., 2009 ; Ghosal et al., 2019 ; Kuya et al., 2019 ). However, in vitro studies have shown that this period can vary from 4-15 days depending on the purpose of investigation ( Nghi et al., 2019 ; Islam et al., 2022 ; Thapa et al., 2022 ; Shanmugam et al., 2023 ). We selected a 14-day period to capture the period up to the emergence stage, which is crucial for evaluating seedling vigor and emergence, ultimately reflecting coleoptile elongation.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-one days is a commonly used duration for AG evaluation under flooded soil conditions ( Ismail et al., 2009 ; Ghosal et al., 2019 ; Kuya et al., 2019 ). However, in vitro studies have shown that this period can vary from 4-15 days depending on the purpose of investigation ( Nghi et al., 2019 ; Islam et al., 2022 ; Thapa et al., 2022 ; Shanmugam et al., 2023 ). We selected a 14-day period to capture the period up to the emergence stage, which is crucial for evaluating seedling vigor and emergence, ultimately reflecting coleoptile elongation.…”
Section: Methodsmentioning
confidence: 99%